Pengaruh Ukuran Perusahaan, Profitabilitas, Leverage, Kompleksitas Operasi, Dan Ukuran Kap Terhadap Audit Delay (Studi Empiris Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia Periode 2013-2015) - Murdiono, Berkah, Dra. Rina Trisnawati, AK, M.Si. PhD (2017)
The aim of this study was to determine the effect of company's size, profitability, leverage, the complexity of the operation, and KAP size. To audit audit delay in manufacturing companies listed on the Indonesia Stock Exchange during the period of 2013-2015. The sample are 219 companies were obtained by purposive sampling technique. The data analysis technique used was logistik regression. The results showed that the profitability variables gave significant effectto the audit delay, while variable company's size, leverage, the complexity of the operation, and KAP size didn't affect the audit delay.